(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
This article examines the implementation of a personalized AI-based monetization system in the Uzbek gaming industry. Particular attention is paid to recommendation systems as a tool for increasing revenue for local studios and developing the digital economy. A review of international practices and their potential for adaptation to the local context is provided, along with proposals for integrating AI technologies into game development processes. Using analytical and survey methods, this study serves as a foundation for subsequent applied research and practical recommendations.